2022
DOI: 10.1159/000520288
|View full text |Cite
|
Sign up to set email alerts
|

The Bacteriology of Skin Lesions in Patients with Hidradenitis Suppurativa Is Associated with Previous Antibiotic Treatment in the Community Setting: A Referral Center Experience

Abstract: <b><i>Background:</i></b> Hidradenitis suppurativa (HS) is a chronic skin disease characterized by inflammatory nodules and abscesses. The pathogenic role of bacteria is not fully understood. As the diagnosis is usually delayed, patients are often treated with several lines of antibiotics in a nonstandardized fashion. The aim of the study was to investigate and compare the bacteriology of active HS lesions in patients treated or not treated with antibiotics in the community setting befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Across eleven studies, the diagnosis of HS after initial presentation of symptoms ranged from 3 to 10 years with most studies finding a delay of 6 to 10 years. [18][19][20][21][22][23][24][25][26][27][28] Two studies that focused only on patients diagnosed prior to 2013 found the average delay also around 7 years. 18,19 Recent studies from 2017 to 2020 showed similar findings, with an average delay of 10 years, indicating that diagnostic delay remains an ongoing barrier to care for patients with HS.…”
Section: Diagnostic Delay In Hsmentioning
confidence: 99%
“…Across eleven studies, the diagnosis of HS after initial presentation of symptoms ranged from 3 to 10 years with most studies finding a delay of 6 to 10 years. [18][19][20][21][22][23][24][25][26][27][28] Two studies that focused only on patients diagnosed prior to 2013 found the average delay also around 7 years. 18,19 Recent studies from 2017 to 2020 showed similar findings, with an average delay of 10 years, indicating that diagnostic delay remains an ongoing barrier to care for patients with HS.…”
Section: Diagnostic Delay In Hsmentioning
confidence: 99%
“…In HS lesions, the limited epidermal upregulation of antibacterial proteins enables the propagation of the microbes in the skin [ 20 , 41 , 42 ]. The persistent presence of bacterial components supports the chronic inflammation through the stimulation of monocytes/macrophages/dendritic cells via their innate immune receptors (i.e., pattern recognition receptors, PRRs) [ 41 , 43 ].…”
Section: Role Of Neutrophilic Granulocytes In Hs Lesionsmentioning
confidence: 99%